Photosynthesis - From Its Evolution to Future Improvements in Photosynthetic Efficiency Using Nanomaterials 2018
DOI: 10.5772/intechopen.75519
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Photosynthesis under Pulsed Lighting

Abstract: The effects of pulsed irradiation based-LEDs on the growth and photosynthetic light utilization efficiency of lettuce leaves were studied. Plants were grown under different pulse-cycled irradiations of 0.5-500 Hz, and 1-20 kHz frequencies, at PPFD of 200 μmolm À2 s À1 with 50% duty ratio (illuminated duration/cycle). The photosynthetic rate (Pn) was maintained relatively constant over the range of measurements at pulsed light at 80 PPFD. At 200 PPFD, Pn gradually decreased by lowering frequency below 2.5 Hz of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…For instance, Jishi et al [ 22 ] explored the effects of pulsed LEDs at different frequencies (0.1, 0.2, 0.4, 0.8, 1.6, 3.2, 6.4, 12.8 kHz; 75% duty ratio) on romaine lettuce and did not find a significant effect on net photosynthesis compared to continuous light. Kanechi [ 12 ] found that photosynthetic rate of lettuce under pulsed light (0.5–500 Hz, 1–20 kHz, 50% duty ratio) was slightly higher than that under continuous light, and this is consistent with our results. The observed effects of pulsed-light parameters on net photosynthesis could be explained by the pooling of photosynthetic intermediates [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For instance, Jishi et al [ 22 ] explored the effects of pulsed LEDs at different frequencies (0.1, 0.2, 0.4, 0.8, 1.6, 3.2, 6.4, 12.8 kHz; 75% duty ratio) on romaine lettuce and did not find a significant effect on net photosynthesis compared to continuous light. Kanechi [ 12 ] found that photosynthetic rate of lettuce under pulsed light (0.5–500 Hz, 1–20 kHz, 50% duty ratio) was slightly higher than that under continuous light, and this is consistent with our results. The observed effects of pulsed-light parameters on net photosynthesis could be explained by the pooling of photosynthetic intermediates [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…The results [ 1 ] demonstrated that pulsed LED treatment with a 75% duty factor has no inhibition on the growth of lettuce as compared to continuous light, and a pulsed light treatment at 1 kHz was the most effective in terms of growth as well as energy use efficiency. Furthermore, pulsed light at high frequencies (2–20 kHz, 50% duty factor) positively affects the growth of lettuce under controlled environmental conditions [ 12 ]. The pulsing ability of flexible LED lighting systems to produce sufficient photon fluxes of specific wavelengths can be linked with characteristics of photosynthesis and satisfy the photosynthesis requirements [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches directly switch the current flowing through the LED on and off using a PWM signal, resulting in a dynamic but pulsed control of the light intensity [ 26 ]. Employing such pulsed control for growing or studying plants is problematic as it may impact the physiological processes of the plants [ 20 ]. While our method also uses PWM, it is only used as control feedback for the power supply and the current to the LED is kept constant.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of the PWM modulation is usually well above that for the human perception of flicker (which is about 25 Hz) and the perceived brightness depends on the duty-cycle. While PWM is often used in illumination engineering it is not suited for plant growth; some studies indicate that using PWM to control irradiance can induce physiological responses [ 20 ]. Therefore, the use of CCR is preferred to control irradiance in plant research unless the aim is to provide irradiance in the form of repetitive pulses.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of the PWM modulation is usually well above that for the human perception of icker (which is about 25 Hz) and the perceived brightness depends on the duty-cycle. While PWM is often used in illumination engineering, it is not suited for plant growth; some studies indicate that using PWM to control irradiance can induce physiological responses (19). Therefore, the use of CCR is preferred to control irradiance in plant research unless the aim is to provide irradiance in the form of repetitive pulses.…”
Section: Methodsmentioning
confidence: 99%